Castellated Steel Beams Efficiency by Topology Optimization - Andaryati Ruseno; Yoki Triwahyudi (Civilla : Jurnal Teknik Sipil Universitas Islam Lamongan, 2022)
The IWF structure of castellated beams has developed its application along with advances in manufacturing technology which is applied to commercial and industrial buildings, especially the use of wide span beams and high rise buildings that require many beam openings as heating, ventilation and air conditioning (HVAC) lines. Castellated beam has the advantageous characteristics of cross-sectional inertia and larger cross-sectional modulus than the original IWF steel beam. In addition, it has the ability to carry a greater moment with greater stiffness.The purpose of this topology optimization is to produce the optimum layout and opening of the body plate which has a smaller weight or volume but has greater stiffness. Optimization is done by using a linear analysis of Finite Element Analysis (FEA). Topology optimization gives us optimum results and a clear result of the initial design (shape, width of openings and number of openings) resulting from the objective function (minimization of weight or volume) and the constraint function (structural stiffness, stress, displacement and volume ratio).To determine the relationship between the layout model based on shape density, stiffness ratio and volume ratio, a finite element topology optimization study for IWF steel profiles of 300x150x6.5x9 will be carried out with several volume ratio constraints of 0.5; 0.4 and 0.3. Topology optimization results will be validated and compared with the use of castellated beam product industry PT.Gunung Garuda Steel Group which is widely used in the Indonesian market.